Bohemian rhapsody: performance, ritual e relações de gênero no breaking - Joana Brauer Gonçalves (2012)
This thesis examines the performance, ritual and gender relations of the Hip Hop dance culture illustrated originally by breaking. Based on the analysis of the conditions of Hip Hop insurgence, and of its main manifestations (breaking, graffiti, MC, DJ), this study explores dance as a cultural manifestation for anthropology, and evaluates the non verbal language of the dance and of its dancers. The focus of this exploratory study is placed on the battle of breaking a unique and special moment and its foundations in performances studies, communication studies, semiotics, and anthropology of dance. Furthermore, the thesis explores breaking and its performance, which involves not only dancing movements but also the gender of the dancer, vestments, and the gestures of b-boys and b-girls. Finally, we analyze the ritualized performance of the battle and the performing effectiveness of the dancers. Throughout this study, dance is understood as a language in action, through which it is possible to convey a message in an autonomous fashion, without the support of verbal communication, reaching profound meaning that is unattainable by words. This is the power of breaking in the act of speaking the unspeakable and of making comprehensible the common experience of competition, aggressiveness, and of the gender relations in the urban context of large cities.